TEKNOLOGI ULTRAFILTRASI UNTUK PENGOLAHAN AIR TERPRODUKSI (PRODUCED WATER) - Henny Ikka Safitri; Fella Ryanitha A.; Nita Aryanti (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Produced water generated from crude oil exploitation contains compounds such as BTEX, ammonia, phenol, and mercury that are dangerous for human health and environment. Some technologies have been applied for produced water treatment such as biological wastewater treatment with microorganism, coagulation and flocculation. In this research, produced water was treated using ultrafiltration membrane. Specifically this research is aimed to obtain characteristic of produced water and ultrafiltration membrane (functional groups in membrane), to determine the membrane performance (flux and rejection) and the effect of ultrafiltration on the final characteristic of produced water. Characterization of produced water showed that the COD, TOC, toluene, and xylene content exceed the minimum values of wastewater quality standards for oil, gas, and geothermal activities. Membrane analysis using SEM showed the polyethersulfone membrane having an asymetric membrane structure. FTIR analysis showed there were aromatic components of SO2, PVP, and OH stretching group in the membrane. In variation of pressure, the permeate flux of PES decrease 2,5% for 1 bar, and 59% for 2 bar. In addition, PES can reject 96,8% COD, 99,9% TOC, 83% toluene, and 94,6% xylene. This research demonstrated that ultrafiltration was capable for produced water treatment since the effluent can meet the government quality standards of water disposal for COD and TOC contents